Improvement of fatigue, physical functioning, and well-being among patients with severe impairment at baseline receiving ibrutinib in combination with bendamustine and rituximab for relapsed chronic lymphocytic leukemia/small lymphocytic lymphoma in the HELIOS study. Issue 9 (2nd September 2018) - Cramer, Paula; Fraser, Graeme; Santucci-Silva, Rodrigo; Grosicki, Sebastian; Dilhuydy, Marie-Sarah; Janssens, Ann; Loscertales, Javier; Rule, Simon; Goy, Andre; Traina, Shana; Chan, Eric K. H.; Diels, Joris; et al.
Abstract: Health-related quality of life (HRQoL) is an important endpoint, especially in clinical trials for malignancies with a long course of disease, such as chronic lymphocytic leukemia (CLL). Patient-reported outcomes were examined in the randomized, double-blind, placebo-controlled HELIOS study to assess the impact of treatment with the Bruton's tyrosine kinase inhibitor ibrutinib, added to bendamustine plus rituximab (BR) background therapy. Measures included FACIT-Fatigue, EORTC QLQ-C30, QLQ-CLL16, and EQ-5D-5L. Of 578 patients enrolled, 540 (93%) provided FACIT-Fatigue responses at baseline. Most had only a moderate degree of impairment at baseline; mean values did not appear to change over time in either treatment arm, suggesting that adding ibrutinib to BR did not impact health-related quality of life. However, post-hoc analyses showed that subgroups of patients with the worst fatigue, physical functional status, and well-being at baseline had greater improvements in these outcomes with ibrutinib plus BR treatment versus placebo.